2019
DOI: 10.1101/826370
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone methyltransferase DOT1L controls state-specific identity during B cell differentiation

Abstract: Differentiation of naïve peripheral B cells into terminally differentiated plasma cells is characterized by epigenetic alterations, yet the epigenetic mechanisms that control B cell fate remain unclear. Here we identified a central role for the histone H3K79 methyltransferase DOT1L in controlling B cell differentiation. Murine B cells lacking Dot1L failed to establish germinal centers (GC) and normal humoral immune responses in vivo. In vitro, activated B cells showed aberrant differentiation and prematurely a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Although understanding the mechanisms in more detail will require further studies, the role of DOT1L in preventing premature differentiation and safeguarding the epigenetic identity is conserved in other lymphocyte subsets. In an independent study ( 75 ), we observed that loss of Dot1L in B cells also led to premature differentiation, perturbed repression of PRC2 targets, and a compromised humoral immune response. Therefore, DOT1L is emerging as a central epigenetic regulator of lymphocyte differentiation and functionality.…”
Section: Discussionmentioning
confidence: 76%
“…Although understanding the mechanisms in more detail will require further studies, the role of DOT1L in preventing premature differentiation and safeguarding the epigenetic identity is conserved in other lymphocyte subsets. In an independent study ( 75 ), we observed that loss of Dot1L in B cells also led to premature differentiation, perturbed repression of PRC2 targets, and a compromised humoral immune response. Therefore, DOT1L is emerging as a central epigenetic regulator of lymphocyte differentiation and functionality.…”
Section: Discussionmentioning
confidence: 76%
“…These findings indicate that AF10 acts as a safeguarding mechanism for somatic cell identity by enabling higher order H3K79 methylation of somatic-specific genes. Presence of higher order H3K79 methylation may antagonize gene repression, thereby preventing silencing of somatic transcriptional programs upon OSKM expression (Stulemeijer et al, 2011)(Aslam et al, 2021). Alternatively, recent work points to a role for DOT1L in transcription initiation, and it will be interesting to investigate if AF10 plays a role in that process (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%